P616 Predictive macrolide and fluoroquinolone resistance markers in mycoplasma genitalium from the UK and ireland. (14th July 2019) - Day, Michaela; Cole, Michelle; Patel, Hemanti; Fifer, Helen; Woodford, Neil; Pitt, Rachel
Abstract : Background: This study sought to assess the prevalence of macrolide and fluoroquinolone resistance in Mycoplasma genitalium -positive specimens received in PHE's national reference laboratory. Methods: M. genitalium -positive clinical specimens submitted from 59 laboratories across the UK and Ireland were tested for molecular markers of macrolide and fluoroquinolone resistance. The 23S rRNA gene and the quinolone-resistance-determining region (QRDR) of parC were amplified by PCR and Sanger sequenced. Single nucleotide polymorphisms (SNPs) associated with clinical treatment failure were detected through sequence alignment in BioNumerics software (V.6.1, Applied Maths, USA). Results: Four hundred and fifty-eight M. genitalium- positive specimens were received between 01/09/17 and 28/11/2018. Sequencing results were available for both gene targets in 389/458 (84.9%) specimens. Seventy-one percent (275/389) were predicted to be resistant to macrolides. 23S rRNA SNPs detected were A2058G (136/275, 49.5%), A2059G (131/275, 47.6%), A2058T (5/275, 1.8%) and A2059C (3/275, 1.1%). Eight percent (31/389) were predicted to be resistant to fluoroquinolones. parC mutations detected were D87N (16/31, 51.6%), S83I (12/31, 38.7%), D87Y (2/31, 6.5%) and S83R (1/31, 3.2%). Seven percent (26/389) were predicted to be resistant to both antimicrobial classes. Only 28% of positive samples tested were predicted to be susceptible to both classes of antimicrobial. Conclusion: Resistance to macrolides, the current first-line treatment for M. genitalium, in specimens received at PHE from patients attending STI clinics in the UK and Ireland is very high, at 85%. Conversely, resistance to the second-line treatment, moxifloxacin, in these specimens was estimated at 8% although the actual rate of resistance may be higher as there are many mutations with unknown treatment outcomes. Isolates exhibiting resistance to both antimicrobial classes are of significant public health concern as further treatment options for this organism are limited. Effective surveillance of SNPs in this organism is imperative to further understand the affect on clinical outcome. Disclosure: No significant relationships.